druckwehrsionen - dokumentation. - Kunstmuseum Düsseldorf (Düsseldorf : Kunstmuseum Düsseldorf, 1981)
Dannhäuser, Artur ; Höptner, Axel ; Lohmann, Julia ; Michalowski, Erwin
druckwehrsionen - dokumentation, Kunstmuseum Düsseldorf, 30.10. bis 22.11.1981
boek